In vitro evaluation of biocontrol agents, botanicals and fungicides against Pestalotiopsis sp. infecting large cardamom (Amomum subulatum Roxb.) - T N Deka, A K Biswas, K A Saju, Smrita Mech (Journal of Spices and Aromatic Crops, 2011)
Commercially available biological control agents (Trichoderma harzianum, T. viride, Pseudomonas fluorescens and Bacillus subtilis), aqueous extracts of plant species (Artemisia vulgaris and Schima wallichi) and four fungicides were screened in vitro at Tadong (Sikkim), against Pestalotiopsis sp. infecting large cardamom (Amomum subulatum). B. subtilis showed significantly high inhibition (62.6%) of the pathogen followed by T. viride (50.9%). Inhibition of mycelial growth of Pestalotiopsis sp. by combined aqueous extract of A. vulgaris and S. wallichi varied from 12.2% to 74.5% and was significantly higher at 15% concentration. Inhibition of the pathogen increased with increase in concentration of the extract. The growth inhibition of the pathogen increased with increase in concentration of all fungicides tested. Carbendazim 50WP was significantly effective at all concentrations tested (0.05%-0.15%). The study indicated the potential of using biocontrol agents and botanicals for eco-friendly management of Pestalotiopsis sp. infecting large cardamom and fungicides in case the incidence is severe.